2020
DOI: 10.1038/s41598-020-70201-z
|View full text |Cite
|
Sign up to set email alerts
|

The molecular insights into protein adsorption on hematite surface disclosed by in-situ ATR-FTIR/2D-COS study

Abstract: Proteins are of ubiquitous interest in the Life Sciences but are of interest in the Geosciences as well because of the significant role these compounds play in the biogeochemical cycling of trace and nutrient elements. Structural changes resulting from the adsorption of proteins onto mineral surfaces may alter protein biological function and other environmental interactions. Iron oxides are major sinks of a range of environmental elements including organic compounds. In this study, the adsorption of the broadl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 115 publications
(140 reference statements)
1
30
0
Order By: Relevance
“…15 Furthermore, past studies have also shown BSA adsorption onto iron-containing mineral oxide surfaces from conformational changes, mainly via electrostatic interactions. 46–48…”
Section: Resultsmentioning
confidence: 99%
“…15 Furthermore, past studies have also shown BSA adsorption onto iron-containing mineral oxide surfaces from conformational changes, mainly via electrostatic interactions. 46–48…”
Section: Resultsmentioning
confidence: 99%
“…The conformational states adopted by oliopeptides and proteins at interfaces can be characterized ATR-FTIR (56)(57)(58)(59)(60)(61). In particular, the Amide I spectroscopic region (1600 -1700 cm -1 ), which arises from stretching vibrations of peptide carbonyl groups, is sensitive to the peptide conformational state (62-64).…”
Section: How Does the Fp1 Sequence Encode Hydrophobic Interactions?mentioning
confidence: 99%
“…27 Similarly, Barreto et al investigated the changes in the secondary structure of protein using in situ ATR/FTIR/2DCOS study. 28 It has been employed in studying the properties of the polymer and provides a way to characterize them. The 2DCOS spectra consist of synchronous ( φ ) and asynchronous correlation spectrum ( ψ ), where the synchronous spectrum consists of auto peaks along the diagonal positions and cross-peaks present at off-diagonal positions.…”
Section: Introductionmentioning
confidence: 99%